Payment Innovations (QR & Instant Systems): A Bibliometric Mapping - Loso Judijanto (West Science Interdisciplinary Studies, 2025)
This study conducts a bibliometric analysis of QR and instant payment systems, focusing on their transformative impact on the financial ecosystem. Using data from Scopus and Web of Science, the research identifies key trends, influential publications, and the interconnections among authors and institutions in the field of payment innovations. QR codes and mobile payment systems have rapidly gained traction due to their efficiency, security, and ability to foster financial inclusion, particularly in regions with high smartphone penetration but limited traditional banking access. The study also explores emerging technologies such as blockchain, artificial intelligence, and machine learning, emphasizing their role in enhancing the security and functionality of digital payments. Despite the growing body of literature, the study highlights the need for further research on the global dynamics of QR and instant payment adoption and provides insights for policymakers and financial institutions to facilitate the transition to a digital-first payment ecosystem.